Public development plan based on coproduction and slow principles: an analytical scheme by action research - Emmendoerfer,Magnus Luiz (2021)
Abstract This study aims to investigate and reflect on the evidence of a development plan based on the coproduction the population and the government of a small municipality, based on the principles of the Slow City Movement (SCM). A descriptive exploratory research was conducted with a qualitative approach. The main guiding strategy of the research, consisted of the action research method carried out in the municipality of Rio Doce, in Minas Gerais, Brazil. The results show that the space for dialogue between the population and the government was relevant and allowed the coproduction of a municipal planning with micro and macro elements and within the slow city principles. Also, traditional practices linked to culture with the use of local environmental resources were included, involving popular knowledge, technologies of social origin and the knowledge of the daily life of the community in a project of future desired by the population.